On the Wrong Track: Process and Content in Moral Psychology. - Kahane, G (2012)
According to Joshua Greene's influential dual process model of moral judgment, different modes of processing are associated with distinct moral outputs: automatic processing with deontological judgment, and controlled processing with utilitarian judgment. This article aims to clarify and assess Greene's model. I argue that the proposed tie between process and content is based on a misinterpretation of the evidence, and that the supposed evidence for controlled processing in utilitarian judgment is actually likely to reflect, not 'utilitarian reasoning', but a form of moral deliberation which, ironically, is actually in serious tension with a utilitarian outlook. This alternative account is further supported by the results of a neuroimaging study showing that intuitive and counterintuitive judgments have similar neural correlates whether or not their content is utilitarian or deontological.